Antibodies to variable Plasmodium falciparum-infected erythrocyte surface antigens are associated with protection from novel malaria infections - Giha, H.A.; Staalsoe, T.; Dodoo, D.; Roper, C.; Satti, G.M.H.; Arnot, D.E.; Hviid, L.; Theander, T.G. (Immunology Letters, 2000)
In areas of unstable transmission malaria affects all age groups, but the malaria incidence is lower in adults compared to children and teenagers. Under such conditions subclinical Plasmodium falciparum infections are common and some infections are controlled, because blood parasitaemia is maintained at low densities. Here, we test the hypothesis that the presence or absence of antibodies against variant antigens on the surface of P. falciparum- infected erythrocytes protect individuals against some infectious challenges and render them susceptible to others. Plasma collected in Daraweesh, eastern Sudan, before and after the malaria season from individuals who had (susceptible) or did not have malaria (protected) during the season, were tested for reactivity against variant antigens on the surface of nine parasite isolates by flow cytometry. Both protected and susceptible individuals acquired antibodies to variant antigens during the malaria season. The presence of antibody to a Ghanaian isolate before the season was statistically significantly associated with protection against malaria. When considering all nine isolates, the patterns of antibody acquisition differed between susceptible and protected individuals. Together, the results indicate that pre-existing anti-PfEMP1 antibodies can reduce the risk of contracting clinical malaria when challenged by novel parasite clones expressing homologous, but not heterologous variable surface antigens. The results also confirm that antibodies to variant antigens are induced by both clinical and subclinical infections, and that antibodies against several var sero-types are induced during an infection. (C) 2000 Elsevier Science B.V.
Keywords: Malaria; Plasmodium falciparum-infected erythrocytes; Sudan; Variant antigens